The atlas 3D Project – XXXI. Nuclear radio emission in nearby early-type galaxies - Nyland, K; Young, L; Wrobel, J; Sarzi, M; Morganti, R; Alatalo, K; Blitz, L; Bournaud, F; Bureau, M; Cappellari, M; Crocker, A; Davies, R; et al. (Oxford University Press, 2016)
We present the results of a high-resolution, 5 GHz, Karl G. Jansky Very Large Array study of the nuclear radio emission in a representative subset of the ATLAS3D survey of early-type galaxies (ETGs). We find that 51 ± 4 per cent of the ETGs in our sample contain nuclear radio emission with luminosities as low as 1018 W Hz-1. Most of the nuclear radio sources have compact (≲25-110 pc) morphologies, although ~10 per cent display multicomponent core+jet or extended jet/lobe structures. Based on the radio continuum properties, as well as optical emission line diagnostics and the nuclear X-ray properties, we conclude that the majority of the central 5 GHz sources detected in the ATLAS3D galaxies are associated with the presence of an active galactic nucleus (AGN). However, even at subarcsecond spatial resolution, the nuclear radio emission in some cases appears to arise from low-level nuclear star formation rather than an AGN, particularly when molecular gas and a young central stellar population is present. This is in contrast to popular assumptions in the literature that the presence of a compact, unresolved, nuclear radio continuum source universally signifies the presence of an AGN. Additionally, we examine the relationships between the 5 GHz luminosity and various galaxy properties including the molecular gas mass and - for the first time - the global kinematic state. We discuss implications for the growth, triggering, and fuelling of radio AGNs, as well as AGN-driven feedback in the continued evolution of nearby ETGs.